IMPACT OF TEACHER FEEDBACK ON STUDENT PERFORMANCE - Eboni Jhei-Ar Paurillo (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Feedback is one of the most powerful influences on learning and achievement, but this impact can either be positive or negative. While feedback is generally considered essential in learning and development, negative impact may have degrading impacts on students’ self-esteem, engagement and motivation, and overall achievement (Hattie & Timperley, 2007). In the Senior High School alone, teacher feedback plays an important role in how the learners perceived the assessment process. They give so much weight to the comments of their teachers and even their nonverbal responses. It is obvious to have been affecting the students either positively or negatively depending on how the teacher manifest the feedbacking itself and it has become instrumental in developing both their cognitive and metacognitive skills, which are essential for academic success. Despite its many benefits, teacher feedback is not without challenges. This descriptive study was conducted on all the Grade 12 learners of a sampled school in the Schools Division of Quezon City. Data were collected by a valid and reliable questionnaire. In total, 93 percent of students confirmed that teacher feedback has highly affected their motivation in the specific subject, and 85 percent claimed that it has impacted their self-esteem which has an indirect effect on their overall performance. In addition, 100 percent of students noted that casting teacher feedback positively is an answer to these challenges. This makes the strategies of the teacher in the giving feedback to learners become crucial in the students’ overall performance. Based on the results, the use of positive feedback is considered as recommendation which is based on the premise that cultivating students’ interest and nurturing their self-esteem largely depend on the way teachers give feedback so that learning could better take place when students are motivated and when they have confidence in themselves.